STRAWBERY MENINGKATKAN HIGH DENSITY LIPOPROTEIN PADA LANSIA DISLIPIDEMIA - I Made Yase; Gabriel Yosse; Uray Chandra (MEDIA ILMU KESEHATAN, 2012)
Background : Approaching the year 2020 cardiovascular disease will become the leadingc ause of death in the worldbefore theage of 65 years.National HealthSurvey in2001 show-edthat deaths due to cardiovascular diseases including coronary heart diseasea mounted to 26.4%, and until now CHD is also amajor cause of premature death. Thus, responsibility for the disease is not only done by the medical worker but also every individual. Recentre search suggests that increasing HDLcholesterol can prevent cardiovascular disease. Anthocyanins that are found invarious plants Including strawberrie may reduce the risk of cardiovascular disease. Purpose : To identify the effect of strawberry juice administration on levels of HDL in old peo-ple with dyslipidemia. Methods : The study designused in this study is quasi experimental research (qua-si experiment) with the type of control group pretest-pos test design that examinesthe influ-enceof strawberry juiceon the levels of HDL in patients with dyslipidemi a by measuring the levels of HDL before treatment and after treatment. The population in this study were old people with dyslipidemia aged 55-65 years old. The population is divided into two groups, which were the control group and test group. The control group did not receive any treatment, while the test group consume strawberry juice for 14 days with a dose of 100g/day. Result : The results in each group obtained by calculating the average difference in thecontrol group and test group. In the control group decreased HDL cholesterol levels of 0.285mg / dl and in the test group there was an increase in HDL cholesterol of 24.582 mg / dl. Conclusion : Juice of strawberries which contain anthocyanin can increase levels of HDL inold people with dyslipidemia Keyword: Strawberries, HDL, dyslipidemia